Changes of the political polarity and the influential factors that affected political decision-making in the election under the new 2017 Constitution in Ubon Ratchathani - moumg-on, pratueng (King Prajadhipok’s Institute Journal, 2020)
With regard to the changes of political polarity and political parties, it was found that not all candidates who had moved from Pheu Thai Party to Palang Pracharat Party were elected as MPs, such as Yotakan Fongngam, daughter of Suphon Fongngam (the former general-secretary of Pheu Thai Party), Cherdsak Phokkunlanon, the son of Adisak Phokunlanon (a former Pheu Thai Party List MP) and Sutthichai Charunnet, a former Pheu Thai MP in 2011. The influential factors that affected the voter’s decisions under the new 2017 Constitution in Ubon Ratchathani can be described as follow: (1) the candidate’s political party, the policy, political ideology (pro or anti-General Prayuth Chan-O-Cha); (2) the budget spent on vote-buying; (3) the individuals. This research found that the election on 24 March 2019 illustrated that vote-buying was no longer the only factor or a necessary and sufficient condition (NSC) to gain victory in the election in Ubon Ratchathani. As a matter of fact, in this election, vote-buying was commonly known to be practised by a group of political parties in most areas in Ubon Ratchathani (carpet bomb was the metaphor used to describe their vote-buying). In other areas, however, the strategy of sandwich vote-buying was found. It meant that if the targeted person does not like the first party, he/she can choose another party that was an ally of the first.